PERSPEKTIF KRIMINOLOGI TERHADAP ORANG DENGAN GANGGUAN JIWA (SKIZOFRENIA) YANG CENDERUNG MENJADI PELAKU KEJAHATAN - Adel A N Radja; Heryanto Amalo; Adrianus Djara Dima (Petitum Law Journal, 2026)
The development of criminal acts in Indonesia is clear evidence that not all crimes are committed by people with normal souls, but people with mental disorders can also commit crimes. The study focuses on 2 main aspects, namely the underlying causal factors of criminal behavior in perpetrators of schizophrenia and the prevention efforts that can be carried out on perpetrators of crimes with schizophrenia. This study uses an empirical legal method, with a qualitative research approach. The results of the study indicate that there are 2 factors causing criminal behavior in perpetrators of mental disorders (schizophrenia), the first is an internal factor, namely the symptom factor of the disease, biological factors, and individual factors. The second is an external factor, namely environmental and social factors, economic factors and cultural factors. The prevention efforts that can be carried out on people with schizophrenia can be in the form of pre-emptive efforts, namely by conducting socialization and counseling, preventive efforts, namely by providing drugs, rehabilitation in the form of therapy and counseling, and repressive efforts carried out by the police in the form of arrest and exile while still paying attention to Article 44 of the Criminal Code in its punishment.